Could BCG Vaccination Induce Protective Trained Immunity for SARS-CoV-2? - Covián, Camila; Retamal-Díaz, Angello; Bueno, Susan M.; Kalergis, Alexis M. (Frontiers in Immunology, 2020)
Trained immunity is a type of non-specific memory-like immune response induced by some pathogens and vaccines, such as BCG, which can confer antigen-independent protection against a wide variety of pathogens. The BCG vaccine has been extensively used to protect against tuberculosis for almost a 100 years. Interestingly, this vaccine reduces children's mortality caused by infections unrelated to Mycobacterium tuberculosis infection, a phenomenon thought to be due to the induction of trained immunity. The SARS-CoV-2 pandemic has infected, as of April 22, 2020, 2,623,231 people globally, causing a major public health problem worldwide. Currently, no vaccine or treatment is available to control this pandemic. We analyzed the number of positive cases and deaths in different countries and correlated them with the inclusion of BCG vaccination at birth in their national vaccination programs. Interestingly, those countries where BCG vaccination is given at birth have shown a lower contagion rate and fewer COVID-19-related deaths, suggesting that this vaccine may induce trained immunity that could confer some protection for SARS-CoV-2.